EFEKTIVITAS PEMBELAJARAN DIGITAL BERBASIS INTERACTIVE FLAT PANEL (IFP) PADA KEMAMPUAN NUMERASI ANAK USIA DINI - Azka Fauziah, Fiola; Nikmah, Khoirotun; Durrotun Nafisah, Aisyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of engagement and understanding of numeracy concepts among early childhood learners due to conventional and less interactive learning methods. This study aimed to analyze the effectiveness of Interactive Flat Panel (IFP)-based digital learning in improving early childhood numeracy skills. This study also examined differences in numeracy abilities before and after the implementation of IFP and its influence on children’s engagement and understanding of numeracy concepts. The study employed a quantitative approach using a pre-experimental one group pretest-posttest design. The subjects were children aged 5–6 years at TK Budi Luhur Sugio. Data were collected through observation, tests, and documentation. Data analysis techniques included descriptive statistics, paired sample t-test, and Pearson correlation test. The results showed that Interactive Flat Panel (IFP)-based digital learning was effective in improving early childhood numeracy skills. There was a significant difference between pretest and posttest results after the implementation of IFP. The use of IFP also had a positive influence on children’s engagement and understanding of numeracy concepts during the learning process. Interactive technology-based learning media were able to create a more active, interesting, and enjoyable learning atmosphere for children.